Frailty Impact during and after Pulmonary Rehabilitation. (3rd September 2021) - Finamore, Panaiotis; Scarlata, Simone; Delussu, Anna Sofia; Traballesi, Marco; Incalzi, Raffaele Antonelli; Laudisio, Alice
Abstract: Frailty is a condition of reduced physiologic reserve common in COPD candidates to pulmonary rehabilitation, however no study has investigated whether frailty impacts the decline that a great part of COPD patients face after the completion of the rehabilitation program. Study objectives are to verify frailty impact on pulmonary rehabilitation outcomes during and after the program. This is a secondary analysis of a longitudinal study. Stable COPD patients GOLD I-III were randomized to a three-month endurance versus endurance and resistance training. Participants performed a multidimensional assessment at baseline, at the end of the rehabilitation program and after six months. Frailty was defined using a two-step approach including PRISMA-7 and Timed "Up and Go" test. Frailty interaction with time was evaluated using generalized least-squared regression models for repeated measures, correcting for potential confounders. Of the 53 participants with a mean age of 73 (SD:8) years 38 (72%) were frail. The mean 6MWD and V'O2peak increased in frail and no frail patients during pulmonary rehabilitation and declined after its completion, while CAT score showed a steep decline during the training, and a mild decline later. Frailty showed a significant interaction with time in terms of 6MWD variation during (β adj:43.6 meters, p-value:0.01) and after (β adj:-47 meters, p-value:0.02) pulmonary rehabilitation; no significant interaction was found in terms of V'O2peak and CAT score variation. In conclusion, frail COPD patients have a higher potential to benefit from pulmonary rehabilitation, but a higher risk to have a steeper decline later. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.1967915 .